Distribution of soil viruses across China and their potential role in phosphorous metabolism - Han, Li-Li; Yu, Dan-Ting; Bi, Li; Du, Shuai; Silveira, Cynthia; Cobián Güemes, Ana Georgina; Zhang, Li-Mei; He, Ji-Zheng; Rohwer, Forest (Environmental microbiome, 2022)
Viruses are the most abundant biological entities on the planet and drive biogeochemical cycling on a global scale. Our understanding of biogeography of soil viruses and their ecological functions lags significantly behind that of Bacteria and Fungi. Here, a viromic approach was used to investigate the distribution and ecological functions of viruses from 19 soils across China. Soil viral community were clustered more significantly by geographical location than type of soil (agricultural and natural). Three clusters of viral communities were identified from North, Southeast and Southwest regions; these clusters differentiated using taxonomic composition and were mainly driven by geographic location and climate factors. A total of 972 viral populations (vOTUs) were detected spanning 23 viral families from the 19 viromes. Phylogenetic analyses of the phoH gene showed a remarkable diversity and the distribution of viral phoH genes was more dependent on the environment. Notably, five proteins involved in phosphorus (P) metabolism-related nucleotide synthesis functions, including dUTPase, MazG, PhoH, Thymidylate synthase complementing protein (Thy1), and Ribonucleoside reductase (RNR), were mainly identified in agricultural soils. The present work revealed that soil viral communities were distributed across China according to geographical location and climate factors. In addition, P metabolism genes encoded by these viruses probably drive the synthesis of nucleotides for their own genomes inside bacterial hosts, thereby affecting P cycling in the soil ecosystems.